The use of fish and macroinvertebrate assemblages and ichthyoparasites as indicators of the health status of Nwanedi and Luphephe rivers in Limpopo Province, South Africa - Mashilwane, Collins Nkotoloane (My University, 2024)
Nwanedi and Luphephe rivers originates from the Soutpansberg mountains and flows downstream through three ecoregions, namely, Soutpansberg 2.01 Ecoregion at an altitude of 1100 m, Limpopo Plain 1.02 Ecoregion in the middle of the catchment, and Limpopo Plain 1.01 Ecoregion where the Nwanedi River meets the Limpopo River. However, due to increasing human interactions and agricultural developments in the lower reaches, there is a need to determine the present ecological state (PES) of this system. The aim of the study was to determine the PES of the Nwanedi and Luphephe rivers based on fish and macroinvertebrate assemblages and the composition of ichthyoparasites from Pseudocrenilabrus philander (Weber, 1897), a fish species that commonly occurs in the middle and upper catchment of the system. The findings were then compared to a previous survey conducted by Angliss et al. (2007) to determine if the state of these rivers has changed over time. This study was conducted at 10 sites traversing the length of the rivers and across the aforementioned ecoregions, within the Soutpansberg 2.01 Ecoregion (sites 1, 2, 3, 4 and 5), Limpopo Plain 1.02 Ecoregion (sites 6 and 7) and Limpopo Plain 1.01 Ecoregion (sites 8, 9 and 10). Field surveys were undertaken during summer (October 2021) and winter (May 2022). Water quality measurements were taken at each site using a handheld multiparameter instrument and water samples collected to analyse nutrients and metal content at an accredited laboratory. Fish were sampled using electroshocking and a cast net. Specimens caught were identified and recorded and thereafter returned live to the environment. These data were used to categorise the respective ecoregions using the Fish Response Assessment Index (FRAI) protocol. Macroinvertebrates were sampled using the South African Scoring System Version 5 (SASS5) protocol and using the Macroinvertebrate Response Assessment Index (MIRAI) method the PES for each ecoregion was determined. Specimens of P. philander were examined for ichthyoparasites and infestation indices calculated to determine if there was a change in parasite load and diversity between the sites caught. Water constituents measured were compared against the acceptable target water quality range (TWQR) prescribed by DWAF (1996a) for aquatic ecosystems. The concentration of NO3 was high in the lower reaches of the river where the aquatic vegetation was denser. All physico-chemical parameters, nutrients and metals content were within the TWQR guidelines across the sites and ecoregions. Fish assemblages’ results revealed Soutpansberg 2.01 Ecoregion to have a high abundance and species richness, with numbers decreasing with altitude. A canonical correspondence analysis (CCA) revealed most fish species in the Soutpansberg 2.01 Ecoregion to be strongly correlated with high oxygen concentrations with only one species in the Limpopo Plain 1.01 strongly associated with water conductivity, total dissolved solids and salinity. The FRAI results indicated the PES of the Nwanedi and Luphephe rivers to be in good or close to natural conditions based on an assigned ecological category (EC) of class A/B calculated for the Soutpansberg 2.01 Ecoregion and fair with an ECs of classes C and D determined for the Limpopo Plain 1.02 and Limpopo Plain 1.01 ecoregions, respectively. When compared to the findings by Angliss et al. (2007) with scores of C, C and D designated for the respective ecoregions, the ecological state reported in this study for the Limpopo Plain 1.02 and Limpopo Plain 1.01 ecoregions would indicate that system conditions have deteriorated over time. With regard to macroinvertebrates a decline in water quality at sites 1, 2, 3 and 7 based on SASS scores and Average Score per Taxon (ASPT) was reported. The ASPT scores reported for sites 4 and 5 indicated natural water quality conditions while those reported for sites 6 and 9 indicated a slight deterioration in water quality. Conversely, the MIRAI results categorised the PES of the Nwanedi and Luphephe rivers as fair with an EC of class D. When compared to the work undertaken by Angliss et al. (2007) the invertebrate communities in these rivers have deteriorated from an EC of class C/D to that of class D. Ichthyoparasites results revealed the Soutpansberg 2.01 Ecoregion had good water quality based on the high prevalence of Cichlidogyrus philander Douëllou, 1993, a gill monogenean specific to P. philander, and poor water quality for Limpopo Plain 1.02 Ecoregion due to the absence of this parasite observed from P. philander collected in this section of the river. In conclusion, water quality was reported to be good in the Soutpansberg 2.01 Ecoregion with conditions deteriorating slightly in the Limpopo Plain 1.02 and Limpopo Plain 1.01 ecoregions. The water quality results were supported by the FRAI, MIRAI and parasite indices findings. The PES of the pooled data for each ecoregion revealed conditions to have deteriorated when compared to the historic work done by Angliss et al. (2007). For comparative purposes future studies should consider doing more frequent surveys using the methods elucidated above when establishing the PES.
Thesis (M.Sc.( Zoology)) -- University of Limpopo, 2024
Keywords: Macroinvertebrate assemblages; Ichthyoparasites; Pseudocrenilabrus philander; Fish species; Water quality biological assessment -- South Africa -- Limpopo; Aquatic invertebrates -- South Africa -- Limpopo; Fishes -- South Africa -- Limpopo